Particulate organic matter in surface sediments of the Laptev Sea (Arctic Ocean): application of maceral analysis as organic-carbon-source indicator. - Boucsein, Bettina; Stein, Ruediger (PANGAEA, 1999)
Surface sediments from the Laptev Sea and adjacent continental slope were studied for their composition of particulate organic matter (OM) by means of maceral analysis. The composition of macerals in sediments gives information about the environment, terrigenous supply from the hinterland, and marine OM. With reference to their biological sources, we distinguish between terrigenous and marine macerals. We found that the particulate OM in the surface sediments of the Laptev Sea is predominantly of terrigenous origin (mean: 78%). However, distinct variations exist when looking in detail. In the shelf area, sediments may contain up to 99% terrigenous OM. Freshwater algae occur directly north of the river mouths, reflecting the strong fluvial influence. Relatively high amounts of marine OM (20-40%) are restricted to the upper continental slope, the Vilkitsky Strait and west of the New Siberian Islands, explained by increased surface-water productivity due to increased fluvial nutrient supply, open-water conditions, and phytoplankton blooms at the ice-edge.
Macerals in surface sediments of the Laptev Sea (Arctic Ocean)
Keywords: Alginite; Alginite, freshwater; ARK-IX/4; AWI_Paleo; BCR; Box corer (Reineck); Coal clasts or fragments; Cutinite; DEPTH, sediment/rock; Dinoflagellate cyst; Fluorescent microscope; Giant box corer; GKG; Huminite; IK9307-3; IK9316-8; IK9318-5; IK9321-4; IK9330-4; IK9338-5; IK9342-5; IK9350-7; IK9367-1; IK9373-8; IK9373A-6; IK93Z2-5; IK93Z3-4; Inertinite; Ivan Kireyev; Laptev Sea; Laptev Sea, Taymyr Island; Liptinite; Liptinite, terrigenous; Liptodetrinite; Maceral, marine; Maceral, mixed; Maceral, terrigenous; Paleoenvironmental Reconstructions from Marine Sediments @ AWI; Polarstern; PS2451-2; PS2453-2; PS2455-3; PS2456-2; PS2458-3; PS2460-3; PS2461-2; PS2462-3; PS2463-3; PS2465-3; PS2467-3; PS2468-3; PS2469-3; PS2472-3; PS2473-3; PS2474-2; PS2476-3; PS2477-3; PS2478-3; PS2481-2; PS2485-1; PS27; PS27/029; PS27/031; PS27/033; PS27/034; PS27/038; PS27/040; PS27/041; PS27/043; PS27/044; PS27/047; PS27/049; PS27/050; PS27/052; PS27/056; PS27/058; PS27/059; PS27/062; PS27/064; PS27/065; PS27/068; PS27/072; Quaternary Environment of the Eurasian North; QUEEN; Sporinite; Terrigenous; Textinite; Transdrift-I; Vilkitsky Strait; Vitrinite